2021
DOI: 10.1186/s13046-021-01830-z
|View full text |Cite|
|
Sign up to set email alerts
|

Hsa_circ_0005273 facilitates breast cancer tumorigenesis by regulating YAP1-hippo signaling pathway

Abstract: Background Circular RNAs (circRNAs), a novel class of endogenous RNAs, have shown to participate in the development of breast cancer (BC). Hsa_circ_0005273 is a circRNA generated from several exons of PTK2. However, the potential functional role of hsa_circ_0005273 in BC remains largely unknown. Here we aim to evaluate the role of hsa_circ_0005273 in BC. Methods The expression level of hsa_circ_0005273 and miR-200a-3p were examined by RT-qPCR in BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…More specifically, circRNAs can regulate the cell cycle by exerting their sponging ability; for instance, circ-ZNF292 inhibits cell proliferation and promotes apoptosis of hepatocellular carcinoma cells by regulating the WNT/β-catenin pathway [ 36 ]. An additional example is circ_0005273 (gene of origin: PTK2 ), which regulates the Hippo/YAP (YAP1) pathway through sponging miR-200a-3p, in order to promote breast cancer tumorigenesis [ 37 ]. Proteins encoded by circRNAs are implicated in signaling regulation as well.…”
Section: Functions Of Circrnas and Their Involvement In Signal Transductionmentioning
confidence: 99%
“…More specifically, circRNAs can regulate the cell cycle by exerting their sponging ability; for instance, circ-ZNF292 inhibits cell proliferation and promotes apoptosis of hepatocellular carcinoma cells by regulating the WNT/β-catenin pathway [ 36 ]. An additional example is circ_0005273 (gene of origin: PTK2 ), which regulates the Hippo/YAP (YAP1) pathway through sponging miR-200a-3p, in order to promote breast cancer tumorigenesis [ 37 ]. Proteins encoded by circRNAs are implicated in signaling regulation as well.…”
Section: Functions Of Circrnas and Their Involvement In Signal Transductionmentioning
confidence: 99%
“…A great many studies have supported that circRNA affects various diseases, like cardiovascular diseases, cancer and neurological diseases [ 6 , 7 ]. Recently, based on ever-growing studies, circRNA is crucial in treating and diagnosing BC [ 8 , 9 ]. CircCNOT2, a recently identified circRNA, is highly expressed in BC.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in the Hippo pathway can result in YAP/TAZ hyperactivation, which may contribute to the occurrence and development of many human diseases, including inflammation, fibrosis, and cancer [ 14 , 32 ]. For instance, abnormal Hippo pathway activation has been observed during breast cancer tumorigenesis [ 33 ]. It has recently been reported that the Hippo/Yap pathway plays a key role in hepatic fibrogenesis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%